Fingertip reconstruction: study of functional and cosmetic results of various local flaps and grafting techniques in patients attending a tertiary care center in North India - Khan, Shameem A.; Kumar, Vivek; Srivastava, Neeraj (International Journal of Research in Medical Sciences, 2019)
Background: Finger injuries are becoming more common with the increasing use of mechanical, industrial, and household appliances. There are six main types of repair for this injury. The replacement of skin loss in digital injuries, particularly on the volar aspects, is an important part of hand-injury management. It would be of value to know the best type of cover, especially for sensory reinnervation as well as for subjective evaluation, cosmetic appearance and freedom from complications. The objective of this study was to measure incidence of age, sex, site, pattern of injury as well as to evaluate and compare the functional and cosmetic results of the various local flap and grafting techniques in finger reconstruction distal to metacarpophalangeal joint. Methods: In a prospective study between May 2014 to October 2018 consisting of 50 patients (43 males, 7 females), aged between 2 years and 54 years, with soft tissue loss distal to metacarpophalangeal joint were treated with either free split-thickness skin grafts, palmar flaps, cross-finger flap or pedicle flaps from the abdomen. The follow-up period ranged from 10 days to 15 months from the date of surgery. Subjective and objective evaluation was done and graded as excellent, good, fair and poor. Results: In this series there were 2 good and 6 fair results for split skin grafting; 9 good and 6 fair results for v-y plasty; 5 excellent, 12 good and 4 fair results for cross finger flap; 1 good and 1 fair result for radial artery based flap; 1 excellent and 1 good for first metacarpal artery based flap and 2 good results for abdominal flap. Overall 6(12%) had excellent, 27(54%) had good and 17(34%) had fair results. None of them had poor results. Conclusions: The group of patients with cross-finger flaps had less subjective complaints and more normal objective testing results than the other groups. When an extensive tactile pad avulsion exists, the cross-finger pedicle flap offers the best long-term result with fewer secondary problems. The exclusive use of any one method cannot be advocated since each serves an useful purpose under proper conditions.